Maqashid Syariah Sebagai Basis Pengembangan Ekonomi Islam - nasfi, nasfi; sabri, Sabri (El-kahfi | Jurnal Ekonomi Islam, 2022)
This study aims to look at the problems of the application of Islamic economics in economic activities with the Maqashid Syariah approach. The research method in this research is field research by means of library research. The research findings from the views of scholars about Maqasid Al-Shari'ah are Maslahat, because the determination of law in Islam must lead to Maslahat as well as in carrying out economic activities carried out by humans, must be oriented to Maslahat. Meanwhile, the research findings from the view of Maqashid Syari'ah in economic development, occupy a very important position in formulating sharia economics, both broadly economic activities and financial activities including Islamic banking, which is the main requirement in ijtihad to answer various problems of economic and finance. Where is the ultimate goal of Islamic economics according to Islamic law itself (Maqashid Asy Syari'ah) to achieve happiness in this world and in the hereafter.